2019
DOI: 10.1177/0956797619844231
|View full text |Cite
|
Sign up to set email alerts
|

Attention Drives Emotion: Voluntary Visual Attention Increases Perceived Emotional Intensity

Abstract: Attention and emotion are fundamental psychological systems. It is well established that emotion intensifies attention. Three experiments reported here ( N = 235) demonstrated the reversed causal direction: Voluntary visual attention intensifies perceived emotion. In Experiment 1, participants repeatedly directed attention toward a target object during sequential search. Participants subsequently perceived their emotional reactions to target objects as more intense than their reactions to control objects. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 39 publications
3
40
0
1
Order By: Relevance
“…Arguably, the current relevance manipulation modulated attentional sampling for task-relevant stimuli, which in turn led to increased impact of these events on momentary affect. These findings are also consistent with research showing that exogenously manipulated attention to an affective stimulus changes the affective experience of that same stimulus [ 26 ] as well as research showing that attentional deployment is one of the fundamental mechanisms behind affect regulation (e.g. [ 36 ]).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Arguably, the current relevance manipulation modulated attentional sampling for task-relevant stimuli, which in turn led to increased impact of these events on momentary affect. These findings are also consistent with research showing that exogenously manipulated attention to an affective stimulus changes the affective experience of that same stimulus [ 26 ] as well as research showing that attentional deployment is one of the fundamental mechanisms behind affect regulation (e.g. [ 36 ]).…”
Section: Discussionsupporting
confidence: 90%
“…The current research concerns the reverse relationship; that is, whether voluntary attentional selection informed by stimulus relevance influences fluctuations in momentary affective experience. Previous investigations showed that previously ignored neutral stimuli are evaluated more negatively than previously attended stimuli [ 25 ] and that previously attended visual images are evaluated as more emotionally intense in comparison with control stimuli [ 26 ]. These findings show that voluntary attentional selection can influence the evaluation of sensory stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…As an important emotional cue, a clearly valenced infant facial expression with a strong emotional intensity could be recognised quickly, and this recognition would be accompanied by enhanced electrocortical responses, helping the adult correctly classify the specific expression type (Peltola et al, 2014). Conversely, recent evidence has revealed that voluntary visual attention resulted in a greater rise in the perceived emotional intensity in response to neutral images (including those of faces) than in response to positive or negative images (Mrkva et al, 2019). Consequently, ambiguously valenced infant facial expressions with a mild emotional intensity may cause an adult's elevated sensitivity by increasing the involvement of limited parenting resources to avoid missing valuable signals, facilitating the infant's survival and development and advancing early parent-child relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Balding and Williams (2016) suggested that intentionally anthropomorphizing and empathizing with plants can lead to more interest in plants, less “plant blindness,” and even more support for plant conservation. There is evidence that visual attention can trigger and engage emotion (Mrkva, Westfall, & Van Boven, 2019) suggesting that attention and attitude are related. In fact, Lindemann‐Matthies (2005) demonstrated that an educational intervention that drew student attention to plants also increased their interest in the plant.…”
Section: Attitudementioning
confidence: 99%